Indywidualne doświadczenia turysty a ekonomia - Marciszewska, Barbara (Individual Experiences of a Tourist Vs. Economics, 2008)
The contemporary world of developed economies attempts to search for more and more efficient methods of goods and services exchange in order to prevent the occurrence of deep crisis resulting from overproduction. The instruments used in market competition are more and more frequently not sufficient for boosting the economy. The introduction of radical changes into the processes of products' creation, in connection with innovative management solutions, might ensure higher level of consumers' satisfaction and, in consequence, a faster consumption growth. According to the theory of Pine II and Gilmore (1999) one of the opportunities for preserving and making an economic growth more dynamic results from a different approach towards the subject of an offer at the market. The above authors point to the need of noticing a "new" market product enriched by human experiences. The objective of the hereby article is to point to post-consumptive experiences of a tourist as a source of value. Such post-consumptive experiences have still not been a fully identified aspect of a product, which in the nearest future may play a key role in boosting the economic effect on the one hand and consumers' satisfaction on the other. The said satisfaction is the source of value in the future production and consumption.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 158-165